Peran Pendidikan Kewirausahaan Dan Love Of Money Terhadap Intensi Berwirausaha Pada Mahasiswa Akuntansi - Agni Astungkara; Rochmi Widayanti (ITB AAS INDONESIA, 2020)
The pattern of accounting education at the university level is often direct the student to fulfill positions at established companies or institutions. The competencies held by accounting graduates should also be directed to support a country's economy through its role in the field of entrepreneurship. It cannot be denied, entrepreneurship is one of the pillars of the country's economy. Therefore entrepreneurial behavior must always be encouraged, one of them through entrepreneurship education. This study will examine the role of entrepreneurship education and the Love of Money towards the intention to entrepreneurship in accounting students. The results showed that entrepreneurship education independently has not been able to encourage intentions for entrepreneurship, but students with high levels of Love of Money have an influence on entrepreneurial intentions. The sample in this study were 70 accounting students at one of the private university in Surakarta. Through this research the university is expected to be able to encourage accounting students to become entrepreneurs, as well as to package the patterns of activities to be more effective and efficient. Keywords: accounting student, entrepreneurship, love of money, entrepreneurship education, entrepreneurship intention, love of money.